Leader's perceptions of the impact of increasing use of e-health services on assessing the need for treatment – qualitative study on secondary care emergency department - Ylilehto, Marja; Liljamo, Pia; Raatiniemi, Lasse; Kanste, Outi (Finnish Journal of eHealth and eWelfare, 2021)
The increasing use of e-health (electronic health) services is changing the way the assessment of need for treatment is implemented in secondary care emergency departments. The assessment of need for treatment refers to the professional's assessment of a patient's need for emergency care. As the use of e-health services increases, the individuals more often assess their own need for treatment with the help of electronic tools before entering the emergency department and without contacting a healthcare professional. The deployment of e-services is challenging without proper understanding of the socio-technical relationship between technology, humans, and the operating environment. The purpose of this study is to describe the leaders’ perceptions on 1) the assessment of need for treatment in the emergency department; 2) the impact of the increasing use of e-health services on the assessment; 3) the preparation for the operational changes due to increased use of e-health services; and 4) the factors influencing the success of the change. The research material was collected during autumn 2019, with thematic interviews of nursing managers and medical directors responsible for the operational management of the secondary care emergency departments in five university hospital districts (n=10). The material was analyzed using qualitative content analysis. The results show that the biggest impact of the increasing use of e-health services are on humans and functions. The work of professionals, the activities of customers, and the assessment of the need for treatment are changing, and the emergency care service is developing. Leaders agree with the socio-technical approach and see the impact of the increasing use of e-services as an operational change that has an effect on the entire emergency department. Preparations for this operational change and the subsequent need for better preparedness have been made, but there are challenges. Preparedness is being promoted and needs to be supported. Successful implementation of operational change is subject to many influencing factors such as attitude, demonstration of benefits, operational environment, and resources. The preconditions for successful deployment of e-services in the assessment of the need for treatment in the secondary care emergency department look optimistic. It is important to prepare for operational change and to consider all factors promoting or hindering its success. Without adequate financial preparedness, the success of operational change can be challenging. The insights of this study can be utilized in the implementation and development of e-services to support the assessment of the need for treatment, anticipating changes in operations and improving management efficiency.